2014
DOI: 10.2337/dc13-2395
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Subcutaneous Fat Cell Volume and Insulin Sensitivity After Weight Loss

Abstract: OBJECTIVELarge subcutaneous fat cells associate with insulin resistance and high risk of developing type 2 diabetes. We investigated if changes in fat cell volume and fat mass correlate with improvements in the metabolic risk profile after bariatric surgery in obese patients. RESEARCH DESIGN AND METHODSFat cell volume and number were measured in abdominal subcutaneous adipose tissue in 62 obese women before and 2 years after Roux-en-Y gastric bypass (RYGB). Regional body fat mass by dual-energy X-ray absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 32 publications
6
62
2
1
Order By: Relevance
“…Our previous study has also reported an interesting finding regarding adipocyte hypertrophy in the L-PGDS KO mice compared with the C57BL/ 6 mice [8]. Simultaneously, it is also believed that decrease in fat cell volume rather than a decrease in adipose tissue mass after marked weight loss improves greater insulin sensitivity [38]. Therefore, we decided to examine the fat size in mice that underwent VSG compared with the sham surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study has also reported an interesting finding regarding adipocyte hypertrophy in the L-PGDS KO mice compared with the C57BL/ 6 mice [8]. Simultaneously, it is also believed that decrease in fat cell volume rather than a decrease in adipose tissue mass after marked weight loss improves greater insulin sensitivity [38]. Therefore, we decided to examine the fat size in mice that underwent VSG compared with the sham surgery.…”
Section: Discussionmentioning
confidence: 96%
“…How could fat cell size play a role in type 2 diabetes? A phenotype characterised by smaller adipocytes, as well as increased adipocyte number in scWAT, correlates with increased insulin sensitivity [27] and a beneficial metabolic profile [28]. Furthermore, genetic predisposition for type 2 diabetes associates with adipocyte hypertrophy in non-obese first-degree relatives [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the same subjects, the sWAT mean fat cell size was determined as described in detail previously30. In 148 subjects (only 4 were lean or overweight), we also performed dual X-ray absorptiometry (DEXA) as described31. In brief, body fat composition was assessed using a GE Lunar iDXA and the software enCORE (version 14.10.022)32 provided by the manufacturer (GE Healthcare, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%